2018
DOI: 10.21608/blj.2018.47583
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of antiproliferative activity of Capparis spinosa L extract against Ehrlich ascites carcinoma in Swiss albino mice

Abstract: Background: Medicinal plants have been known as one of the most important therapeutic agents for cancer treatment and prevention. Capparis spinosa L is a multipurpose plant that contains different bioactive phytochemicals including phenols and flavonoids.Aims: In the present study we explore the invivo antitumor activity of Capparis spinosa L extract and most potent constituents rutin and hesperidin against Ehrlich ascites carcinoma (EAC). Also study the side effect of treatments on different organs (liver, ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
2
2
0
Order By: Relevance
“…Despite the improvement of renal function in the EAC-bearing mice treated with Cis, the levels of urea and creatinine were still significantly elevated from those of the control values. Similar findings have also been reported in recent studies [ 21 , 44 , 45 ]. Indeed, nephrotoxicity is a common side effect of Cis medication that may be due to the impairment of renal functions, the back-leakage of the renal tubules, and/or renal tubular obstruction induced by Cis [ 39 , 46 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Despite the improvement of renal function in the EAC-bearing mice treated with Cis, the levels of urea and creatinine were still significantly elevated from those of the control values. Similar findings have also been reported in recent studies [ 21 , 44 , 45 ]. Indeed, nephrotoxicity is a common side effect of Cis medication that may be due to the impairment of renal functions, the back-leakage of the renal tubules, and/or renal tubular obstruction induced by Cis [ 39 , 46 ].…”
Section: Discussionsupporting
confidence: 93%
“…These findings partially correlated to previous studies of Donia et al [ 16 ], who suggested that Hesp exerted antitumor properties and possessed an ameliorative effect against doxorubicin cytotoxicity, while enhancing its antitumor effect, attributing this to the ability of Hesp to arrest tumor growth via the apoptotic pathway by downregulating the expression of Bcl-2, an antiapoptotic gene, and upregulating the expression of the Caspase3 and Bax genes, apoptotic genes. Another study explained that the antitumor mechanism of Hesp may be mediated by the induction of apoptosis and prevention of oxidative damage [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results obtained aligned with many earlier studies that demonstrated the transplantation of EAC into the mouse group increased serum levels of urea and creatinine, which may be related to renal damage brought on by the tumor's catabolic action as a result of cancer cell invasion (Abo-Neima et al, 2023;Mohammed et al, 2018;Sindhuri et al, 2023).…”
Section: Discussionsupporting
confidence: 88%
“…Creatinine and urea are two of the conventional test indices for kidney functions and renal structural integrity (Mohammed et al., 2018). In the current study, kidney function was estimated by measuring serum urea and creatinine concentration.…”
Section: Discussionmentioning
confidence: 99%